A long‐term study of temporal variation in wing feather mite (Acari: Astigmata) infestations on robins, Erithacus rubecula, in Nottinghamshire, UK. (12th January 2022) - Peet, R.; Kirk, A.; Behnke, J. M.
Abstract: European robins ( Erithacus rubecula ) were mist netted and assessed for wing feather mite infestations in north‐east Nottinghamshire, England from June 1998 until March 2014. We analysed records of 899 first capture birds using three measures of infestation: prevalence of mites (% showing evidence of infestation), number of wing feathers infested with mites on one wing (NIWF), and the total mite infestation score (TOTMIS). The latter is the sum of scores (range 0–4) allocated to each of the 19 flight feathers on the assessed wing. The overall prevalence of infestation was 90.9% (95% confidence limits = 88.19–93.02), and average NIWFs and TOTMIS (±sem ) were 6.0 ± 0.15 and 6.5 ± 0.23, respectively. All three measures varied significantly between age classes of birds, but not between the sexes, and varied markedly between months of the year. TOTMIS values were highest in late winter/early spring months and then dropped markedly in May to a low in summer months (usually by August), the dip in abundance of mites coinciding with the breeding season of robins. The best mixed‐effects generalised statistical model was one that comprised month of capture and age of birds but there was also a highly significant negative correlation between TOTMIS values of individual birds and the mean monthly ambient temperature in the month of capture as well as that of the preceding month. The most parsimonious interpretation of our data is that the highly consistent dip in mite abundance on adult robins from spring to summer months reflects vertical transmission of mites to their nestlings/fledgelings. These results are discussed in the context of the biology of both hosts and mites. Abstract : We studied the prevalence and abundance of wing feather mites on robins in Nottinghamshire monthly over 14 years. Our data show consistent reductions in both measures during the breeding season and we hypothesise that this is a case of vertical transmission of mites from parents to their offspring.